Highly Sensitive Two-Photon Lipid Droplet Tracker for in Vivo Screening of Drug Induced Liver Injury - Lee, Hyo Won; Lee, In Jeong; Lee, Soo Jin; Kim, Yu Rim; Kim, Hwan Myung (ACS Sensors, 2022)
Lipid droplets (LDs) are lipid-abundant organelles found in most cell lines and primarily consist of neutral lipids. They serve as a repository of various lipids and are associated with many cellular metabolic processes, including energy storage, membrane synthesis, and protein homeostasis. LDs are prominent in a variety of diseases related to lipid regulation, including obesity, fatty liver disease, diabetes, and atherosclerosis. To monitor LD dynamics in live samples, we developed a highly selective two-photon fluorescent tracker for LDs (LD1). It exhibited outstanding sensitivity with a remarkable two-photon-action cross section (φδmax> 600 GM), photostability, and low cytotoxicity. In human hepatocytes and in vivo mouse liver tissue imaging, LD1 showed very bright fluorescence with high LD selectivity and minimized background signal to evaluate the stages of nonalcoholic fatty liver disease. Interestingly, we demonstrated that the liver sinusoid morphology became narrower with increasing LD size and visualized the dynamics including fusion of the LDs in vivo. Moreover, real-time and dual-color TPM imaging with LD1 and a two-photon lysosome tracker could be a useful predictive screening tool in the drug development process to monitor impending drug-induced liver injury inducing drug candidates.
Keywords: Cell lines; Fatty liver disease; In-vivo; In-Vivo imaging; Lipid droplets; Liver injuries; Neutral lipid; Phospholipidosis; Steatosis; Two photon; Animals; Chemical and Drug Induced Liver Injury; Hepatocytes; Lipid Droplets; Lipids; Mice; fatty liver disease; in vivo imaging; lipid droplets; phospholipidosis; steatosis